Hemodynamic investigation and in vitro evaluation of a novel mixed‐flow blood pump. Issue 8 (22nd February 2022) - Qu, Yifei; Guo, Ziyu; Zhang, Jing; Li, Guiling; Zhang, Song; Li, Donghai
Abstract: Introduction: Ventricular assist devices (VADs) are considered an effective treatment for patients with advanced heart failure, while complications associated with blood damage remain a burden. Structure design innovation has the potential to reduce hemolysis and improve hemocompatibility. Methods: In this research, a novel mixed‐flow blood pump that integrates structural features of the axial and centrifugal VADs was proposed. The pump consists of an inducer, a mixed impeller supported by two ceramic pivot bearings, and a volute. The flow field and laminar viscous shear stress were analyzed by the in silico simulation. The hydraulic and hemolytic performance were evaluated in vitro by using a 3D printed pump. Results: The flow field distribution showed that streamlines in the connection area were smoothly transitioned through structural integration and no irregular flow occurred in the entire flow channel. The axial blades work as a fluid accelerator (generating 18.56% of the energy), and the centrifugal blades provide the main pressure head. The proportion of fluid inside the pump exposed to low laminar viscous shear stress (<50 Pa) and high laminar viscous shear stress (>150 Pa) was 99.02% and 0.03%, respectively. The in vitro hemolysis test results showed that the NIH (Normalized Index of Hemolysis) value of the mixed pump is 0.0079 ± 0.0039 g/100 L ( n = 6). Conclusion: It can be concluded that the mixed flow structure is effective at improving hydraulic performance, eliminating flow disturbance, and minimizing shear stresses. This novel pump design is expected to provide a new direction for the development of next‐generation VADs. Abstract : A novel mixed‐flow blood pump that integrates structural features of the axial and centrifugal VADs was proposed. The hemodynamic behaviors analyzed in silico showed that streamlines were smoothly transitioned through structural integration and no irregular flow occurred. Furthermore, the hemolytic results evaluated in vitro by using a 3D printed pump showed that the NIH (Normalized Index of Hemolysis) value is 0.0079 ± 0.0039 g/100 L ( n = 6).